Cold snare polypectomy without submucosal injection: safety and efficacy in 615 large serrated lesions - Roberto Augusto Barros; Maria Jose Monteverde; Jean-Marc Dumonceau; Augusto Sebastian Barros; German Luis Rainero; Roberto Federico Barros; Maria Jose Jaroslavsky; Santiago de Elizalde (Endoscopy International Open, 2021)
Background and study aim Cold resection is becoming the standard of care for the resection of nonpedunculated colon lesions up to 10 mm in diameter. Sessile serrated adenomas/polyps (SSA/Ps), including those ≥ 10 mm, present various characteristics that make them ideal candidates for cold snare polypectomy (CSP). Patients and methods A prospectively maintained database was searched retrospectively for consecutive patients with lesions ≥ 10 mm resected between March 2013 and March 2018. During that period, all SSA/P-appearing lesions were resected using CSP without submucosal injection, except for lesions with endoscopic suspicion of dysplasia or submucosal invasion. Patients with a pathological diagnosis of SSA/P were included in the analysis. Adverse events were recorded up to 21 days following colonoscopy. Results 615 SSA/Ps ≥ 10 mm were resected during 452 colonoscopy procedures in 379 patients (mean age 54.1 years; standard deviation [SD] 11.9 years). Mean polyp size was 13.7 (SD 5.2) mm; 122 lesions (19.8 %) were ≥ 20 mm and 479 lesions (77.9 %) underwent piecemeal resection. Immediate adverse events included persistent abdominal pain that resolved spontaneously within 2 hours in three patients (0.8 %; 95 % confidence interval [CI] 0.2 %–2.3 %). One patient with persistent intraprocedural bleeding was successfully treated with a hemostatic clip. No late adverse events were detected. Surveillance colonoscopy was performed in 293 patients (77.3 %) at 23.4 (SD 11.6) months following index colonoscopy; residual/recurrent lesions were diagnosed in 23 patients (7.8 %; 95 %CI 5.0 %–11.6 %). Conclusion CSP without submucosal injection appeared to be safe and effective for the resection of large SSA/Ps.